Indonesia Digital Public Diplomacy on @kemlu_ri Instagram: Benefit and Challenges during COVID-19 - Puja Resma Nelam Sari (Jurnal Riset Manajemen Komunikasi, 2021)
Abstract. Communication and information systems have crucial roles during this uncertain pandemic era. The practice of public diplomacy demands a fast reconfiguration for efficiency in using digital communication to reach wider audiences. A trusted source of information is a must. At the same time, international cooperation is elusive to defeat the COVID-19 pandemic. Each nation's reputation and credibility are also put to the test through its actions and words. Previous studies stated, digital diplomacy is part of a communication revolution. This paper will be focused on state actors as legitimate sources. This paper seeks to address digital communication as an approach to digital diplomacy on Instagram. It describes the features Instagram has to offer. This paper explains Indonesia's benefit and challenge to increase digital communication use on Instagram as public diplomacy. Abstrak. Sistem komunikasi dan informasi memiliki peran yang sangat krusial dalam era pandemi yang tidak menentu ini. Praktik diplomasi publik menuntut konfigurasi ulang yang cepat untuk efisiensi masing-masing dalam menggunakan komunikasi digital untuk menjangkau khalayak yang lebih luas. Sumber informasi terpercaya adalah suatu keharusan. Pada saat yang sama, kerja sama internasional sulit dilakukan untuk meredakan dan mengalahkan pandemi COVID-19. Reputasi dan kredibilitas setiap negara juga diuji melalui tindakan dan perkataannya. Pernyataan masalah sebelumnya, diplomasi digital merupakan bagian dari revolusi komunikasi. Makalah ini akan difokuskan pada aktor negara sebagai narasumber yang sah. Makalah ini berupaya membahas komunikasi digital sebagai pendekatan diplomasi digital di Instagram. Ini melibatkan fitur yang ditawarkan Instagram. Namun, tulisan ini menjelaskan manfaat dan tantangan Indonesia untuk meningkatkan penggunaan komunikasi digital di Instagram sebagai diplomasi publik.